Ease Of Use of The Dana E-Wallet Application in Costumer Satisfaction an Pee Store - Resty Oktarisna; Iswidana Utama Putra; Aji Sudarsono (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Peestore Bengkulu, as one of the MSMEs, has implemented a digital payment system using DANA through QRIS. Most transactions in this store are conducted cashless, with DANA as the most dominant application used. This condition is influenced by the characteristics of consumers, the majority of whom are students and productive age groups who do not have bank accounts, so they choose DANA because it is easily accessible, practical, and has no monthly administration fees. This phenomenon became the basis for conducting research to analyze the effect of the ease of use of the DANA E-Wallet on consumer satisfaction. This study used a quantitative approach with a causal associative method on 97 respondents selected purposively, namely consumers who had transacted using DANA at the Peestore. The ease of use variable was measured through several main indicators, while consumer satisfaction was measured through indicators ranging from overall satisfaction to recommendation intention. The analysis was conducted through validity and reliability tests, simple linear regression, coefficient of determination, and t-test. The results showed that all instruments were valid and reliable (Cronbach's Alpha > 0.90). Descriptively, ease of use (3.77) and customer satisfaction (3.82) are in the high category. The regression equation Y = 2.517 + 0.946X with R² of 0.835 shows that 83.5% of customer satisfaction is influenced by ease of use. The t-test (21.943; sig 0.000) proves that there is a positive and significant effect.